Analysis of Tensile Loads on Metal Inert Gas Welding Spiral Steel Pipe 508 - Hotman Sihombing, Rudi Adolf (Malikussaleh University, Aceh, Indonesia, 2024)
Welding is one of the most widely used material joining techniques in various industries, including automotive, construction, and manufacturing. MIG (Metal Inert Gas) welding and SMAW (Shielded Metal Arc Welding) are the most commonly used welding methods. Both have different processes, speeds, quality of welding results, and application characteristics, but this research will apply it to MIG welding. This research aims to determine the difference in the ultimate tension tensile test (Tu) on a 12 mm thick spiral steel pipe 508 pipes when planted for 10 years and a new 12 mm thick spiral steel pipe 508. From the research results, it can be concluded: that it turns out that the value of the Ultimate Tension (Tu) on the new Spiral Steal Pipe 508 pipe is more significant than that which has been installed, with the average value of the Ultimate Tengan (Tu) on the new Spiral Steal Pipe 508 pipe being 498.72 N/mm2, while the average value of the Ultimate Tension (Tu) on the old Spiral Steal Pipe 508 pipe is 476.49 N/mm2. There is a difference in the Ultimate Tension (Tu) value of 0.95%; this is caused by changes in the structure of the Spiral Steal Pipe 508 pipe, which has been planted for 10 years.